2022
DOI: 10.1111/nph.18102
|View full text |Cite
|
Sign up to set email alerts
|

The effects of arbuscular mycorrhizal fungal species and taxonomic groups on stressed and unstressed plants: a global meta‐analysis

Abstract: The great majority of plants gain access to soil nutrients and enhance their performance under stressful conditions through symbiosis with arbuscular mycorrhizal fungi (AMF). The benefits that AMF confer vary among species and taxonomic groups. However, a comparative analysis of the different benefits among AMF has not yet been performed.We conducted a global meta-analysis of recent studies testing the benefits of individual AMF species and main taxonomic groups in terms of plant performance (growth and nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 85 publications
2
31
0
Order By: Relevance
“…the abundance of Diversispora AMF (Guo et al, 2021). Moreover, a recent meta-analysis reported that the AMF benefits on plants varied among species and taxonomic group, with Diversisporales being the most beneficial to plants (Marro et al, 2022). Based on these findings, we could primarily attribute the great benefits of inoculum D to the high abundance of Diversisporaceae.…”
Section: Plant Mycorrhizal Responses Depend On the Combination Of Hos...mentioning
confidence: 87%
“…the abundance of Diversispora AMF (Guo et al, 2021). Moreover, a recent meta-analysis reported that the AMF benefits on plants varied among species and taxonomic group, with Diversisporales being the most beneficial to plants (Marro et al, 2022). Based on these findings, we could primarily attribute the great benefits of inoculum D to the high abundance of Diversisporaceae.…”
Section: Plant Mycorrhizal Responses Depend On the Combination Of Hos...mentioning
confidence: 87%
“…AMF play essential roles in plant resistance subjected to various environmental stress and could potentially help farmers reduce the crop yield losses in the changing global climate [ 32 , 35 , 71 , 72 ]. Here we investigate, to the best of our knowledge for the first time, the multifaceted roles of a new combination of AMF species in the alleviation of salt, drought, and cold stress in peanut plants.…”
Section: Discussionmentioning
confidence: 99%
“…Despite both experimental duration and plant R/S being important in the prediction of the effect size of AMF on the plant shoot, root, and total biomass, we found that the correlations of these two moderators with the effect size were all weak. This might be due to the numerous factors that can influence the functions of AMF, including plant and/or AMF species ( Marro et al., 2022 ), plant nutrition status, and experimental light intensity ( Johnson, 2010 ). Accordingly, these weak relationships might be the result of the different experimental factors, which should be taken into consideration in future research.…”
Section: Discussionmentioning
confidence: 99%